Duduk & Tonton 3: Online Screening and Discussion with Filmmakers - Yow, Chong Lee; Yong, Stacy Wan Wei (Mini Film Festival, 2021)
Programmed by Gayatri Nadya (Kolektif, Indonesia), this screening featured 6 short films made by Malaysian filmmakers, namely: 1) Fitrah by Yulinda Dwi Andriyani 2) Maria Ado'E by Gleinda Stefany 3) Folksong by Wimar Herdanto 4) Rumah di Belakang Rumah by Indra Hermawan 5) Pengantin by Rizki Fahrizalmi